Metapsicologia e clínica psicanalítica: um estudo sobre as relações entre os princípios clínicos e as construções metapsicológicas - Barbelli, Izabel Cristina (2011)
Research on the Freudian psychoanalysis epistemological characteristics demands an analysis focused on the criteria that Freud established the constituent experimental parameters of the construction and validation processes of metapsychological concepts, as an analysis on the rationality nature that underlies the conceptual outline structure of metapsychological theory, from the search for endopsychic laws formulated by logical articulation of the results obtained in clinical practice. Therefore, the research objective is to examine whether or not these criteria may provide an effective reference to the human psychic reality, to this theory, indeed.